2019
DOI: 10.1111/bld.12299
|View full text |Cite
|
Sign up to set email alerts
|

What are the perspectives of adolescents with Down syndrome about their quality of life? A scoping review

Abstract: Accessible summary• This study looked for information about the quality of life of adolescents with Down syndrome.• We found two studies about quality of life that included the voice of the adolescent with Down syndrome. Most of the research includes parents' voices. Parents' views are important, but we need to also include adolescents with Down syndrome in research about their lives. • Friends, family and independence are important to adolescents with Down syndrome. • More information on quality of life is ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 56 publications
(87 reference statements)
0
10
0
Order By: Relevance
“…The lowest scores were observed in self-determination and social inclusion, and this is despite the importance of personal autonomy and social participation (Scott et al, 2014;Sheridan et al, 2020;van Gameren-Oosterom et al, 2011) in people's lives. The low scores could be explained by possible overprotection and the lack of opportunities experienced by people with DS (Callus et al, 2019;Polo et al, 2020), by their family's lack of time to facilitate community participation (Shields et al, 2020), and by the lack of supports, adaptations, and programs to forge self-determination skills and promote effective social inclusion Scott et al, 2014).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The lowest scores were observed in self-determination and social inclusion, and this is despite the importance of personal autonomy and social participation (Scott et al, 2014;Sheridan et al, 2020;van Gameren-Oosterom et al, 2011) in people's lives. The low scores could be explained by possible overprotection and the lack of opportunities experienced by people with DS (Callus et al, 2019;Polo et al, 2020), by their family's lack of time to facilitate community participation (Shields et al, 2020), and by the lack of supports, adaptations, and programs to forge self-determination skills and promote effective social inclusion Scott et al, 2014).…”
Section: Discussionmentioning
confidence: 92%
“…Even so, it should be noted that the views of family members and other close contacts when assessing the QoL of people with ID is not only common (e.g., Shields et al, 2018; Xanthopoulos et al, 2017) but also important (Schalock et al, 2021), particularly when dealing with early childhood. To address this limitation, future research should focus on developing a self-report version that enables young people with DS to give their own views on their QoL (Berástegui & Corral, 2020; Palomba et al, 2020; Sheridan et al, 2020). Third, the results of this study show relationships between different predictor variables and QoL scores, but causal relationships were not established.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Table 3 , five of the studies named, applied or proposed specific measurement tools to assess QOL (QOL-Q, Integral Scale, Gencat Scale, Personal Outcomes Scale, Personal Wellbeing Index), self-determination (AIR Self-Determination Scale), or rights (Rights of Persons with Disabilities ad hoc scale). Only one study used qualitative instruments in the form of focus groups and in-depth interviews [ 30 ]. While all of these papers referred to a QOL conceptual framework as a way of evaluating or monitoring the CRPD (Articles 31 and 35), some also focused on other CRPD Articles, the most common being ( n = 2) Article 7 (children with disabilities), Article 19 (living independently and being included in the community), and Article 24 (education).…”
Section: Resultsmentioning
confidence: 99%
“…The parental stress has deleterious effects on the whole family including children and overall family system (Staunton et al, 2020) The result of a study showed that the parents of children with no neurodevelopment problem had higher marital intimacy than the parents having children with Down Syndrome (Carrada et al, 2019). The research also revealed high quality of life among parents of healthy children instead of parents of children with Down Syndrome (Sheridan et al, 2019). It has been also indicated in our findings that quality of life has been disturbed in the parents having children with Down Syndrome.…”
Section: Discussionmentioning
confidence: 99%